2016
DOI: 10.4090/juee.2015.v9n2.127-138
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between extreme rainfall and insurance claims due to urban flooding – case study Fredrikstad, Norway

Abstract: During the last decades an increase in extreme rainfall has led to more urban flooding. This study is based on insurance claims of damages caused by heavy rain during 2006-2012 in Fredrikstad, Norway. Data are analysed using Principal Component Analysis. The purpose has been to find characteristics of extreme rainfall and its influence on the extent of urban flooding. The number of claims seems to be peaked in the late summer period. Furthermore, the precipitation depth the week before an extreme rainfall seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Our findings also align with the results of previous studies (Spekkers et al, 2013;Zhou et al, 2013;Wobus et al, 2014;Torgersen et al, 2015) and further indicate that insurance databases are a promising source for flood-damage assessment at the local (Garrote et al, 2016;Le Bihan et al, 2017;Zischg et al, 2018;Zhou et al, 2013) and regional scale (Barredo et al, 2012;Kim et al, 2012;Wobus et al, 2014;Zhou et al, 2017). However, using insurance data as a unique source for defining flood damage leads to only considering the direct and tangible damage.…”
Section: Valencian Communitysupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings also align with the results of previous studies (Spekkers et al, 2013;Zhou et al, 2013;Wobus et al, 2014;Torgersen et al, 2015) and further indicate that insurance databases are a promising source for flood-damage assessment at the local (Garrote et al, 2016;Le Bihan et al, 2017;Zischg et al, 2018;Zhou et al, 2013) and regional scale (Barredo et al, 2012;Kim et al, 2012;Wobus et al, 2014;Zhou et al, 2017). However, using insurance data as a unique source for defining flood damage leads to only considering the direct and tangible damage.…”
Section: Valencian Communitysupporting
confidence: 90%
“…Future research should focus on incorporating further variables into the model to reproduce the complexity of flood risk, not only regarding hazard drivers but also considering more variables related to the exposure and vulnerability, as for example those related to the buildings present in the study region. Furthermore, the present study only focuses on daily precipitation data, while several studies point out the possible better relationship found between sub-daily data and insurance data in the case of surface water floods (Spekkers et al, 2013;Torgersen et al, 2015;. Nevertheless, the analysis of sub-daily extremes would require convectionpermitting regional climate models (Tramblay and Somot, 2018), and studies such as Beranová et al (2018) have shown that convection is not captured realistically.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
See 2 more Smart Citations
“…25% of the variance of claim frequency could be explained and that the three independent variables most strongly associated to claim frequency were maximum rain intensity, real estate value, and ground floor area. Torgersen, Bjerkholt, Kvaal, and Lindholm (2015) used insurance data and precipitation gauge data to analyse the relationship between extreme rainfall and insured flood damage for the period 2006-2012 in the city of Fredrikstad in south east Norway. The authors found a distinct peak of the a damage amount during the late summer months and the results further indicated that several hours of intense rainfall caused more damage than shorter, extreme rainfall events.…”
mentioning
confidence: 99%